Prevention of hepatocellular carcinoma in chronic viral hepatitis B and C infection - Lu, Tao (Baishideng Publishing Group Co., Limited, 2013)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide, with the majority of cases associated with persistent infection from hepatitis B virus (HBV) or hepatitis C virus (HCV). Natural history studies have identified risk factors associated with HCC development among chronic HBV and HCV infection. High-risk infected individuals can now be identified by the usage of risk predictive scores. Vaccination plays a central role in the prevention of HBV-related HCC. Treatment of chronic HBV infection, especially by nucleoside analogue therapy, could also reduce the risk of HBV-related HCC. Concerning HCV infection, besides the advocation of universal precautions to reduce the rate of infection, pegylated interferon and ribavirin could also reduce the risk of HCV-related HCC among those achieving a sustained virologic response. Recently there has been mounting evidence on the role of chemopreventive agents in reducing HBV- and HCV-related HCC. The continued advances in the understanding of the molecular pathogenesis of HCC would hold promise in preventing this highly lethal cancer.